ANALISIS DETERMINAN NILAI PERUSAHAAN SEKTOR MANUFAKTUR DI BEI TAHUN 2016 -2021 - Wanda Agita Devi; Junaidi Junaidi; Siti Aminah Anwar (Universitas Islam Malang, 2022)
The purpose of this study was to determine 1) the effect of leverage on firm value, 2) the effect of profitability on firm value and 3) the effect of capital structure on firm value. The sampling method in this study used purposive sampling. The sample in this study consisted of 58 manufacturing sector companies listed on the IDX from 2016 to 2021. The data analysis technique used was multiple linear regression. By using the statistical tool package or social science (SPSS) v.28.0 for windows, the results of this study indicate that 1) Leverage has no effect on firm value, 2) profitability has a significant positive effect on firm value, 3) Capital structure has a significant positive effect on firm value. Based on the result of the study, it was concluded that the variable of profitability and capital structure are factors that affect firm value. While the leverage variable is not a factor that affects firm value.Keywords: Leverage, Profitability, Capital Structure and Firm Value.